Analysis of service quality by front office department at Alila Villas Uluwatu - I Kadek Aryatmaja; Ni Nyoman Sri Astuti; Lien Darlina; I Ketut Sutama; Tyas Raharjeng Pamularsih (Politeknik Negeri Bali, 2021)
This study aims to determine the service quality and efforts of the Front Office department at Alila Villas Uluwatu in maintaining and improving the quality of its services. This research used a descriptive statistical analysis with purposive sampling method and collecting data using the method of observation, interviews, literature study, and documentation. The results on this research was the service quality of the Front Office department at Alila Villas Uluwatu are good and optimal. The quality service of Front Office department at Alila Villas Uluwatu based on 5 variables, namely tangible, reliability, responsiveness, assurance and empathy. The analysis results showed that all variables has greater percentage of positive reviews than negative reviews. The advice that can be given is to inform more clearly about the location in each Front Office section such as the lobby and villa.